Analisis Sektor Unggulan Kabupaten Tegal Berdasarkan PDRB Tahun 2016-2021 - Irwan Suliantoro (JURNAL MANAJEMEN KEUANGAN PUBLIK, 2022)
Gross Regional Domestic Product (GRDP) is a parameter that reflects the general welfare of a region. GRDP data can be used to analyze the progress of the economic development of a region in a certain period. The objectives of this research are: 1) To examine the sectors which are the basis for the economic development of Tegal Regency based on the 2016-2021 GRDP; 2) To assess the leading sectors that contribute to the economic development of Tegal Regency based on the 2016-2021 GRDP. The basic sector is the sector that exports its products outside the region. The leading sector is the basic sector whose product growth rate exceeds the growth rate of the same sector in its upper-level region. The research method used in this study is descriptive quantitative which examines GRDP data with Location Quotient Analysis and Dynamic Location Quotient Analysis. The results of the study show that there are 3 leading sectors that contribute to the economic growth of Tegal Regency, namely the Mining and Quarrying sector; sector of Provision of Accommodation and Food and Drink; and the Other Services sector. From the results of the mapping of the leading sectors, it is necessary to formulate a development planning strategy by giving high priority to these three sectors. However, since the total contribution of the three sectors is very small, for the initial stage, the development planning strategy can be focused on the Food and Drink Provision sub-sector. Keywords: Basic Sector, Location Quotient, Dynamic Location Quotient, Tegal